2013
DOI: 10.1017/s0022377813001268
|View full text |Cite
|
Sign up to set email alerts
|

Exact Riemann solver for ideal magnetohydrodynamics that can handle all types of intermediate shocks and switch-on/off waves

Abstract: We have built a code to obtain the exact solutions of Riemann problems in ideal magnetohydrodynamics (MHD) for an arbitrary initial condition. The code can handle not only regular waves but also switch-on/off rarefactions and all types of non-regular shocks: intermediate shocks and switch-on/off shocks. Furthermore, the initial conditions with vanishing normal or transverse magnetic fields can be handled, although the code is partly based on the algorithm proposed by Torrilhon (2002) (Torrilhon, M. 2002 Exact … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…In this way, FD-Prim is algorithmically quite analogous to FVM, in that it first interpolates (rather than reconstructs) high-order Riemann states at each cell interface, then uses them to calculate interface fluxes by solving Riemann problems using either exact or approximate solvers, and finally makes corrections to the fluxes to deliver high-order-accurate FD numerical fluxes [57,60]. In this way the FD-Prim approach allows the added flexibility of choosing a Riemann solver (e.g., exact [66,67,68,33], HLL-types [69,70,71,72], or Roe [73], etc.) in a manner analogous to the FVM approach.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, FD-Prim is algorithmically quite analogous to FVM, in that it first interpolates (rather than reconstructs) high-order Riemann states at each cell interface, then uses them to calculate interface fluxes by solving Riemann problems using either exact or approximate solvers, and finally makes corrections to the fluxes to deliver high-order-accurate FD numerical fluxes [57,60]. In this way the FD-Prim approach allows the added flexibility of choosing a Riemann solver (e.g., exact [66,67,68,33], HLL-types [69,70,71,72], or Roe [73], etc.) in a manner analogous to the FVM approach.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past more than four decades, there have been a large number of numerical investigations for ISs. In spite of evolutionary conditions, ISs are commonly observed to be stable shocks in numerical simulations (e.g., Wu 1987;Wu & Hada 1991;Takahashi et al 2013Takahashi et al , 2014, and two interplanetary ISs have been observed and reported (Chao et al 1993;Feng & Wang 2008). However, both ISs were identified through fitting the R-H relations based on one spacecraft observation.…”
Section: Discussionmentioning
confidence: 99%
“…They are related to the question of the existence and the uniqueness of solutions of some Riemann problems. However, there is a ongoing controversy about the significance of non-regular shocks (and compound waves) in MHD (see Takahashi and Yamada, 2014, for an up-to-date overview of the problem).…”
Section: Convexitymentioning
confidence: 99%